Sub‐minute determination of rifampicin and isoniazid in fixed dose combination tablets by capillary zone electrophoresis with ultraviolet absorption detection. Issue 24 (13th November 2018) - Duarte, Lucas Mattos; Amorim, Tatiane Lima; Chellini, Paula Rocha; Adriano, Luiz Henrique Cantarino; de Oliveira, Marcone Augusto Leal
Abstract: A validated sub minute capillary zone electrophoresis method with direct ultraviolet absorption detection for simultaneous determination of isoniazid and rifampicin in fixed‐dose combination tablets was developed. Background electrolyte was defined based on the analytes effective mobility curve and it was composed by 20 mmol/L of sodium carbonate/sodium bicarbonate at pH 10.2. A careful validation procedure considering the main figures of merit was performed. Regression models were satisfactory for isoniazid and rifampicin, showing no lack of fit within 95% significance interval. Interday and intraday precision were evaluated in standard and sample and slight relative standard deviations were achieved for concentration, area, and migration time. Recovery values for accuracy in two levels were 99.97 and 90.08% for isoniazid and 95.45 and 95.12% for rifampicin. The limits of detection for isoniazid and rifampicin were 0.22 and 0.34 mg/L, respectively, and the limits of quantification were 0.74 and 1.13 mg/L, respectively. Method selectivity was verified by injecting diluent, background electrolyte, a standard mixture, and a sample, confirming no interferent peaks. The method proved to be simple, environmentally friendly, sensitive, and was successfully applied for simultaneous quantification of isoniazid and rifampicin in fixed‐dose combination tablets.